From image to trust: Cross-national pathways to brand evangelism in hospitality sector - Ngo Cao Nghia; Phan Khanh Duy; Bao Quoc Truong-Dinh (PLoS ONE, 2026)
This study investigates how frontline employee attributes foster customer brand evangelism in ASEAN hospitality, addressing whether symbolic brand image or relational trust better explains advocacy and under what conditions these mechanisms vary across cultures. A two-wave survey design was implemented with 428 hotel guests in Vietnam and Thailand. Using PLS-SEM and multi-group analysis, the model tested digital competence, proactive assistance, and relationship-building as antecedents of brand evangelism, mediated by brand image and customer trust, and moderated by loyalty program participation and visit frequency. Results reveal dual pathways: brand image and trust both mediate employee behaviors, with symbolic cues dominating in Vietnam and relational credibility prevailing in Thailand. Loyalty programs strengthened trust-based evangelism in Thailand, while visit frequency shaped image-based evangelism differently across contexts. These mechanisms explained substantial variance in evangelism, underscoring cultural contingencies in advocacy formation. This research advances brand evangelism theory by integrating symbolic and relational mediators, identifying boundary conditions, and demonstrating cultural contrasts. It provides a novel dual-process, cross-national framework that refines relationship marketing and social identity perspectives while offering actionable guidance for culturally adaptive hospitality strategies.